The emergence of norms from conflicts over just distributions - Luis M. Miller; Heiko Rauhut; Fabian Winter (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
Why is it that well-intentioned actions can create persistent conflicts? While norms are widely regarded as a source for cooperation, this article proposes a novel theory in which the emergence of norms can be understood as a bargaining process in which normative conflicts explain the finally emerging norm. The theory is tested with a dynamical experiment on conflicts over the consideration of equality, effort or efficiency for the distribution of joint earnings. Normative conflict is measured by the number of rejected offers in a recursive bargaining game. The emerging normative system is analyzed by feedback cycles between micro- and macro-level. It is demonstrated that more normative cues cause more normative conflict. Further, under the structural conditions of either simple or complex situations, the convergence towards a simple and widely shared norm is likely. In contrast, in moderately complex situations, convergence is unlikely and several equally reasonable norms co-exist. The findings are discussed with respect to the integration of sociological conflict theory with the bargaining concept in economic theory.
Keywords: Z13; C91; D63; 330; social norms; normative conflict; bargaining; cooperation; experiment; Soziale Norm; Sozialer Konflikt; Verhandlungstheorie; Test; Verteilungsgerechtigkeit